The Impact of Perceived Ease of Use, Perceived Usefulness, and Trust on Users’ Intention to Use QRIS on BCA Mobile in Surabaya - Inggrid Destrina; Indah Respati Kusumasari (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study is based on technological advancement that have brought significant changes and contributions to various sectors, including finance. One such development is the adoption of financial technology, which integrates finance and technology to enhance efficiency and convenience for users. This research employs a quantitative method with an associative approach. The sampling technique used is purposive sampling, with a total of 150 respondents. Data were analyzed using the PLS-SEM (Partial Least Squares Structural Equation Modeling) method with the help of SmartPLS version 4.0.9.9. The results show that perceived ease of use has no significant effect on usage intention. Meanwhile, perceived usefulness and trust have a significant effect on the intention to use the QRIS feature in the BCA Mobile application in Surabaya.